2016
DOI: 10.4178/epih.e2016002
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fasting glucose, single-nucleotide polymorphisms, and risk for colorectal cancer in Koreans

Abstract: OBJECTIVES:Numerous studies have demonstrated that fasting serum glucose (FSG) levels and certain single-nucleotide polymorphisms (SNPs) are related to an increased risk of colorectal cancer (CRC); however, their combined effects are still unclear. METHODS:Of a total of 144,527 men and women free of cancer at baseline, 317 developed CRC during 5.3 years of follow-up. A case-cohort study (n = 1,691) was used, consisting of participants with a DNA sample available. Three well-known SNPs (rs3802842, rs6983267, rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The high glucose concentration in culture media was correlated with increased glucose uptake in cells as previously shown by radioassay (49, 50) and also represented conditions of hyperglycemia or colonic sugar retention. A higher risk of CRC recurrence was linked to diabetes (1618), whereby patients if not treated properly could display high levels of blood glucose (10–30 mM). Given that colonic retention of dietary sugars due to enteric malabsorption was observed in cancer patients (19), the strategic location of colonic tumors which allows for multiple routes of glucose delivery may compromise treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high glucose concentration in culture media was correlated with increased glucose uptake in cells as previously shown by radioassay (49, 50) and also represented conditions of hyperglycemia or colonic sugar retention. A higher risk of CRC recurrence was linked to diabetes (1618), whereby patients if not treated properly could display high levels of blood glucose (10–30 mM). Given that colonic retention of dietary sugars due to enteric malabsorption was observed in cancer patients (19), the strategic location of colonic tumors which allows for multiple routes of glucose delivery may compromise treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence showed that hyperglycemia and high sugar content in the intestinal lumen enhanced tumor growth and compromised treatment effectiveness in mouse models (14, 15). Increased risk of recurrence and mortality of CRC has also been related to high dietary glycemic load, fasting hyperglycemia, and diabetes (1618). Malabsorption and colonic retention of dietary sugars were found in CRC patients undergoing chemotherapy (19, 20), indicating that high glucose supply from both blood circulation and colonic lumen may promote CRC growth and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…The pain-education nursing based on mind mapping effectively improved patient comfort; when combined with conventional pain care, this process enhanced the body's defense ability and quality of life in patients. [17] Patients with colorectal cancer may experience marked pain during treatment due to related lesions and the anticancer treatment process. [18] Patients experience decreased appetite, reduced resistance, and sleep disorders that greatly impact their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The Korean Cancer Prevention Study II (KCPS-II) included 270 514 Koreans (153 372 men and 117 142 women) who underwent a health examination at 1 of 18 assessment centers in South Korea; the design and methodology of KCPS-II are described in detail elsewhere. 11,12 Of the participants, 17 806 finished an exercise treadmill test at the Severance Health Promotion Center, a KCPS-II participating center between 1994 and 2008. Among them, 14 805 who met the inclusion criteria of age >30 years and had available data on blood analysis, smoking status, alcohol intake, and regular exercise were selected for the present study.…”
Section: Methodsmentioning
confidence: 99%